Mesenchymal Stem Cell–Sourced Exosomes as Potentially Novel Remedies for Severe Dry Eye Disease - Carl Randall Harrell; Valentin Djonov; Ana Volarevic; Aleksandar Arsenijevic; Vladislav Volarevic (Journal of Ophthalmology)
Severe dry eye disease (DED) is an inflammatory condition characterized by a lack of sufficient moisture or lubrication on the surface of the eye, significantly impacting the quality of life and visual function. Since detrimental immune response is crucially responsible for the development and aggravation of DED, therapeutic agents which modulate phenotype and function of eye-infiltrated inflammatory immune cells could be used for the treatment of severe DED. Due to their potent immunomodulatory properties, mesenchymal stem cells (MSCs) represent potentially new remedies for the treatment of inflammatory eye diseases. The majority of MSC-sourced bioactive factors are contained within MSC-derived exosomes (MSC-Exos), nano-sized extracellular vesicles which, due to their nanosize dimension and lipid envelope, easily by pass all biological barriers in the body and deliver their cargo directly into the target immune cells. MSC-Exos contain a variety of bioactive proteins (growth factors, immunoregulatory molecules, cytokines, and chemokines) lipids, and microRNAs (miRNAs) which affect viability, proliferation, phenotype, and function of eye-infiltrated immune cells. Accordingly, MSC-Exos may modulate the progression of inflammatory eye diseases, including DED. Therefore, in this review article, we summarized the current knowledge regarding molecular and cellular mechanisms which were responsible for trophic, anti-inflammatory, immunoregulatory, and regenerative properties of MSC-Exos in the treatment of severe DED. For this purpose, an extensive literature review was carried out in February 2024 across several databases (Medline, Embase, and Google Scholar), from 2000 to the present. Eligible studies delineated molecular and cellular mechanisms responsible for the MSC-Exos–based modulation of immune cell–driven eye inflammation in DED, and their findings were analyzed in this review. Results obtained in these studies demonstrated beneficial effects of MSC-Exos in the treatment of severe DED, paving the way for their future clinical use in ophthalmology.